ʻAlī Shariʻatī on the Crises of Modernity (Al-Qamar, 2023)
Modernity is one of the most prominent & eminent discourses of the post-colonial Muslim ummah; a challenge that threatened the existence & survival of Muslim societies around the globe, regardless of culture & nationality. Islamic modernity & its intellectuals emerged & debated the vital & delicate issue of modernity; this discourse included the impact of modernity on Muslim societies as it confronted Muslim civilization. Dr. Ali Shari'ati is one of the most outstanding thinkers, philosophers & interpreters of Islamic thought. He presented a social vision of Islam, identifying degenerating factors that led to the backwardness & stagnancy of Muslim societies. Shari'ati’s discourse on modernity reflects what the Muslim civilization could take away from modernity, as well as what it had to contribute to it in the form of the emerging idea of “Islamic Modernity”. He emphasized the need to launch a religious renaissance based on the understanding of the concept of man, god, humanity & the inter-connectivity of these elements in the light of Islamic & Qur’anic teachings to develop a dynamic interpretation of Islam that can enter into dialogue with modern intellectual trends.
Keywords: Ali Shariati; Modernity; Islamic Modernity; Iranian Scholarship; Modernity Discourse